Seminal Plasma Antioxidants Are Related to Sperm Cryotolerance in the Horse - Jaime Catalán; Iván Yánez-Ortiz; Asta Tvarijonaviciute; Luis Guillermo González-Aróstegui; Camila P. Rubio; Isabel Barranco; Marc Yeste; Jordi Miró (MDPI AG, 2022)
The objective of this study was to determine the relationship of enzymatic (superoxide dismutase, SOD; glutathione peroxidase, GPX; catalase, CAT; and paraoxonase type 1, PON1) and non-enzymatic antioxidants (measured in terms of: Trolox equivalent antioxidant capacity, TEAC; cupric-reducing antioxidant capacity, CUPRAC; and ferric-reducing ability of plasma, FRAP), as well as the oxidative stress index (OSI) in seminal plasma (SP) with the resilience of horse sperm to freeze-thawing. Twenty-one ejaculates (one per individual) were collected and split into two aliquots: the first was used to harvest the SP and assess the activity levels of antioxidants and the OSI, and the second one was cryopreserved. The following post-thaw sperm quality parameters were evaluated: sperm motility, plasma membrane and acrosome integrity, mitochondrial membrane potential, intracellular levels of reactive oxygen species (ROS), and plasma membrane lipid disorder. Based on post-thaw total motility (TM) and plasma membrane integrity (SYBR14+/PI−), ejaculates were hierarchically (p < 0.001) clustered into two groups of good (GFE) and poor (PFE) freezability. The SP activity levels of PON1, SOD, and TEAC were higher (p < 0.05) in GFE than in PFE, showing a positive relationship (p < 0.05) with some sperm motility parameters and with plasma membrane (PON1 and TEAC) and acrosome (SOD and TEAC) integrity. In contrast, OSI was higher (p < 0.05) in the SP of PFE than in that of GFE, and was negatively correlated (p < 0.05) to some sperm motility parameters and to plasma membrane and acrosome integrity, and positively (p < 0.05) to the percentage of viable sperm with high plasma membrane lipid disorder. In conclusion, enzymatic (PON1 and SOD) and non-enzymatic (TEAC) antioxidants of SP are related to horse sperm cryotolerance. In addition, our results suggest that PON1 could be one of the main antioxidant enzymes involved in the control of ROS in this species. Further investigation is needed to confirm the potential use of these SP-antioxidants and OSI to predict sperm cryotolerance in horses.